Students' Perception on The Implementation of The Whole Brain Teaching Technique in Speaking Class - Nur Kholifah; Aan Erlyana Fardhani; Made Adi Andayani T. (EFL Education Journal, 2021)
Abstract This research aimed to determine the students’ perception on the implementation of the Whole Brain Teaching Technique in speaking class and its benefits for the students at SMPN 2 Banyuanyar Probolinggo. The subject was the seventh grade students who were taken from two classes. This research applied the descriptive quantitative method by using close-ended questionnaire consisting of 34 statements. It was analyzed statistically to know the category of students’ perception. The result of the questionnaire showed that the students had positive perception on the implementation of the Whole Brain Teaching Technique in speaking class. It showed that the total score of the students’ questionnaire was 2594. If the score of the questionnaire was between >2125 up to <2762,5 then it was considered as positive perception. Besides, the implementation of the Whole Brain Teaching Technique gave some benefits for the students. It can be seen from the result of the highest percentage and mean score which were analyzed by using Data Analysis Toolpak in Microsoft Excel. The result showed that the highest percentage and mean score were 3,6 (92%) for the statement “Class-yes help the students to get their attention back”, 3.4(98%) for the statement “Teach-Okay help them remember the material easily”, 3.4 (96%) for the statement “Mirror Technique help them remember and understand the material easily”, and 3.3 (100%) for the statement “Swicth Technique give the same chance for the students to be the speaker and the listener. It means that the implementation of this technique give some benefits for the students. In summary, the students’ perception of the implementation of the Whole Brain Teaching Technique in speaking class was positive and it also provided some benefits for the students during its implementation.